Periodic Wave Solutions and Their Limits for the Generalized KP-BBM Equation - Ming Song; Zhengrong Liu (Journal of Applied Mathematics)
We use the bifurcation method of dynamical systems to study the periodic wave solutions and their limits for the generalized KP-BBM equation. A number of explicit periodic wave solutions are obtained. These solutions contain smooth periodic wave solutions and periodic blow-up solutions. Their limits contain periodic wave solutions, kink wave solutions, unbounded wave solutions, blow-up wave solutions, and solitary wave solutions.